Biodegradation of Used Engine Oil by Acinetobacter junii TBC 1.2 - Witono Basuki; Khairul Syahputra; Ayu Tri Suryani; Ilham Pradipta (Indonesian Journal of Biotechnology, 2011)
The isolates have capability to degrade used engine oil was obtained from soil in the beach contaminatedwith used engine oil. One of the selected isolates TBC 1.2 was identified by its 16s rDNA as Acinetobacterjunii. The microorganism can use hydrocarbons in used engine oil as the sole carbon source and energy, alsoit significantly degraded almost all hydrocarbon compounds in used engine oil. With its ability Acinetobacterjunii TBC 1.2 has a potency to be utilized for bioremediation of soil polluted with used engine oil.